2022
DOI: 10.3389/fonc.2022.888999
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival With Surgical Treatment of Primary Lung Lesions in Non-Small Cell Lung Cancer With Brain Metastases: A Propensity‐Matched Analysis of Surveillance, Epidemiology, and End Results Database

Abstract: ObjectivesNon-small cell lung cancer (NSCLC) with Brain metastases (BM) is an advanced disease with poor prognosis and low survival rate. Our study evaluated the survival benefit of primary lung resection with mediastinal lymph node dissection in NSCLC patients with BM using Surveillance, Epidemiology, and End-result (SEER) databases.MethodsAll cases analyzed were from Surveillance, Epidemiology, and End Results database. The data of the patients with BM of NSCLC from 2010 to 2016 was retrospectively analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Patients aged younger with less comorbidities and well-supported socioeconomically are more likely to tolerate aggressive local treatment to both primary lung lesions and BM, and thus might warrant better survival. [15,25] When narrowing down the study population to those who received primary lung tumor resection, similar results were indicated as mentioned above (Table 3).…”
Section: Prognostic Factors Associated With Prolonged Survivalsupporting
confidence: 71%
See 1 more Smart Citation
“…Patients aged younger with less comorbidities and well-supported socioeconomically are more likely to tolerate aggressive local treatment to both primary lung lesions and BM, and thus might warrant better survival. [15,25] When narrowing down the study population to those who received primary lung tumor resection, similar results were indicated as mentioned above (Table 3).…”
Section: Prognostic Factors Associated With Prolonged Survivalsupporting
confidence: 71%
“…In a retrospective study, the data of 203 NSCLC patients with BM who received primary pneumonectomy plus mediastinal lymphadenectomy and a 1:2 matching control group were extracted from the SEER database. [15] Propensity scoring match (PSM) was applied to minimize selection bias. It is suggested that patients who get thoracic surgery had a better median survival time than those without thoracic surgery in the control group (27 months, 95%CI 19.3-34.7 vs 6 months 95%CI 4.4-7.6).…”
Section: Survival After Primary Lung Tumor Resectionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related death globally, and LUAD is the most common subtype ( 13 ). The popularization of spiral chest computed tomography (CT) has facilitated the diagnosis of patients with early-stage lung cancer ( 5 , 14 ). Nevertheless, because of the insidious onset of lung cancer, many patients already have mid-/late-stage cancers when they are diagnosed, thereby missing the optimal surgical timing, or requiring persistent anti-tumor therapy postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the insidious onset, LUAD patients are commonly diagnosed at an advanced stage, resulting in loss of the opportunity for surgical treatment. The introduction of targeted therapy and immunotherapy has greatly improved the survival outcomes of patients with advanced LUAD ( 5 , 6 ). Hence, searching for more biomarkers of LUAD is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer, breast cancer, and melanoma have been reported to have a higher risk of brain metastases than other types of cancers [ 1 - 3 ]. Brain metastases develop in 30%-50% of patients with non-small cell lung cancer (NSCLC), which severely affect their overall survival [ 4 ]. An increasing number of patients with breast cancer develop brain metastases, especially those with HER2-positive or triple-negative tumors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%